A Base-Mediated Approach Towards Dihydrofuro[2,3-b]Benzofurans from 2-Nitrobenzofurans and 1,3-Dicarbonyls - Singh, Gurdeep; Pandey, Rajat; Kurup, Adarsh S.; Anand, Ramasamy Vijaya (Wiley, 2021)
A straight-forward approach for the synthesis of a dihydrofuro[2,3-b]benzofuran derivatives has been achieved through a base-mediated Michael addition of 1,3-dicarbonyls to 2-nitrobenzofurans followed by intramolecular cyclization. A variety of 1,3-dicarbonyls, including cyclic as well as trifluoromethylated ones, have been subjected to react with 2-nitrobenzofurans under optimal conditions, and the respective dihydrofuro[2,3-b]benzofurans could be accessed in moderate to excellent yields.
Only IISERM authors are available in the record.
Keywords: Dihydrofuro[2,3-b]Benzofurans; 2-Nitrobenzofurans; 1,3-Dicarbonyls